PERAN KELOMPOK TANI DALAM KEGIATAN USAHATANI KAKAO DI DESA KETULUNGAN KECAMATAN SUKAMAJU KABUPATEN LUWU UTARA - Ulfa Lestari; Megawati Idris (Jurnal Agribisnis Indonesia, 2019)
The formation of farmer groups will make it easier for farmers to carry out their farming activities. This study aims to examine the role of farmer groups in cocoa farming activities in Ketulungan Village. The approach used in this study is a qualitative descriptive approach. Respondents were cocoa farmer groups selected using a purposive method. Data collection is done by in-depth interviews with respondents and informants. The informants in this study were extension agents both from related institutions and from the private sector. The results of this study indicate that the role of farmer groups in farming activities includes: (1) Farmer groups as a forum for sharing information, namely farmer groups disseminating information obtained from instructors to their members through meetings; (2) Farmer groups as a place of discussion, namely farmer groups as a place to find solutions to problems in cocoa farming activities such as maintenance and handling of pests and diseases; (3) Farmer groups as a forum for learning, namely farmer groups as a place to get knowledge about cocoa cultivation; (4) Farmer groups as production units, namely farmer groups as providers of facilities and infrastructure in farming activities of their members such as providing fertilizer and cocoa seeds; (5) Farmer groups as a place of cooperation, namely farmer groups capable of cooperating with extension agents, PT Mars and its members in carrying out their farming activities. It is expected that farmer groups, more actively collaborate in farming activities and can cooperate with the government and other parties to improve their farming activities.